Early Experience of Cardiac Surgery in the Maldives - Sapkota, Ranjan; Shafiu, Mohamed; Razzag, Dusooma A; Patil, Priyanka B; Sadoon, Haytham M Y; Abouhabiba, Karim M; Vivehananthan, Sivaranjani P; Shinde, Dipti S; Moosa, Mohamed F; Sattar, Fathmath A A; Gautam, Mani P; Bhadauria, Prateek S; et al. (Journal of Institute of Medicine Nepal, 2019)
Introduction:From stitching a heart wound to the current level of sophistication, cardiac surgery has come a long way as a discipline. Heart surgery in South Asia has advanced tremendously; both, quantitatively and qualitatively. This is a report of the first fifteen surgeries done in the Maldives where cardiac surgery has started as an organized program. Methods: Data on the first fifteen consecutive cardiac surgeries done in our hospital, over a period of 7 months, was analyzed. We briefly describe our usual perioperative management, and the pretext of the beginning of the cardiac surgery program. Results: Fifteen patients, 13 males, aged 59.9±13.8 years, with a EuroScore of 0.9±0.4%, were operated. Eleven underwent CABG; and four had a valve replacement. Nine out of 11 had TVD, including 6 who had an LMCA disease. The first surgery was an off-pump CABG. The CABG group had a total of 2-5 grafts. Pump and cross-clamp times were 239.6 (± 56.1) min and 154.2 (± 45) min respectively. Five (33.3%) had at least one non-fatal complication. Two (13.2%) required re-exploration for mediastinal bleeding. The length of hospital stay was 16.5 days (±6.9 days). The chest tubes stayed for an average of 4.8 (±0.7) days. There was no in-hospital, 30-day and 90-day mortality recorded. Conclusion: Cardiac surgery has begun in the Maldives. It is safe and feasible to sustain cardiac surgery program in the country, provided continued national support and international collaboration is ensured.